Factors Affecting Student Compliance in Asynchronous Classes of the Grade 11 Students - Guavis, Jeenadine; Zaballero, Adrienne (JPAIR Institutional Research, 2022)
Students’ compliance has long been a recurring problem for educators in the academe. In Online Distance Learning, compliance-based activities are the main output teachers generate students’ grades from. Hence, students’ submissions during synchronous and asynchronous sessions are highly expected. This study aimed to ascertain the factors affecting Student Compliance, and the student’s commitment to submit tasks and outputs within the given time, as required in a course, in Asynchronous Classes of the Grade 11 Students of DLSZ-Vermosa. Eighty-six students and three English teachers were respondents to this mixed-methods research. Qualitative data collected from open-ended questions and focus group discussions among teachers and students were coded into categories thematically. Students’ performance in terms of compliance was measured through documentary analysis of the recorded number of output submissions via Google Classroom and Google Spreadsheet record, respectively. Factors affecting student compliance were determined through a researchers-constructed 5-point Likert scale questionnaire. Results revealed that Personal Constraints, Resource Constraints, and LMS/Instruction constraints do not significantly affect the students’ compliance in asynchronous classes. Among the four factors, only the environment or physiological constraints significantly influence the students’ compliance in asynchronous classes. Thus, the extent of the effect of the environment or physiological constraints is moderate to students’ compliance in asynchronous classes.